Antioxidant Assessment of Albizia lebbeck SLNs - Kavitha, S K; Mohammad, Ali; R, Bharathi D; S, Yogesh H (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim: Nanotechnology is pivotal in the pharmaceutical industry, significantly augmenting drug properties and formulations. It enhances drug stability and controlled release, providing precise control over drug delivery systems, thereby maximizing therapeutic efficacy and minimizing adverse effects. Solid Lipid Nanoparticles (SLNs), composed of solid lipids, amalgamate lipid-based systems with nanotechnology to furnish controlled drug release, targeted delivery, and enhanced protection for encapsulated drugs. The integration of antioxidants within SLNs has been shown to enhance their efficacy in addressing diseases associated with oxidative stress. However, including the well-known antioxidant plant Albizia lebbeck leaf extract in the SLNs has been scarcely explored. Materials and Methods: The current study encapsulated the ethanolic extract from the leaves of Albizia lebbeck using stearic acid and polyvinyl alcohol. The encapsulated substance underwent microstructural, morphological, and chemical analysis using FE-SEM, FTIR, and BET techniques. A comprehensive study on antioxidant properties and MTT assay on C6 cells followed standard protocols. Results: The antioxidant properties of the drug were rigorously evaluated using various scavenging assays, including DPPH, superoxide, hydroxyl, nitric oxide, and hydrogen peroxide. The drug exhibited scavenging activity with an IC₅₀ value of 03.07±0.04 μg/mL, 60.51±0.13 μg/mL, 65.57±0.21 μg/mL, 66.06±0.19 μg/mL, and 9.35±0.7 μg/mL, respectively, when compared with ascorbic acid. Although it was less effective than the strong antioxidant ascorbic acid in all assessments, it showed enhanced therapeutic potential, particularly in neurological diseases such as Alzheimer's. The MTT assay on C6 cells found that SLNA concentration from 12.5 to 200 mg/mL initiated apoptosis through cell disintegration, shrinkage, and reduced production of apoptotic bodies. However, it did not induce toxicity compared to the negative control, even at higher dosages. Conclusion: SLNA holds significant potential for advancing pharmaceutical formulations and therapies where controlled antioxidant release is required, particularly in managing neurological diseases.
Keywords: Albizia lebbeck; Anti-oxidant Release; Nanotechnology; Neurological Diseases; Pharmaceutical Formulations; Solid Lipid Nanoparticles